S135 The clinical impact of Streptococcus pneumoniae serotype shift to non-PCV13 vaccine serotypes. (12th November 2019) - Hyams, C; Amin, Z; Ladhani, S; Malin, A; Maskell, NA; Finn, A; Williams, OM
Abstract : Introduction: Conjugate vaccines reduce Streptococcus pneumoniae vaccine serotype circulation with replacement with non-vaccine serotypes. The clinical impact of this remains uncertain, in particular how adult pneumococcal disease may have changed following the replacement of PCV7 with PCV13 in the UK universal childhood programme in 2010. Objectives: To define characteristics of adults hospitalised with pneumococcal disease in Bristol and Bath over a 10 year period spanning 2010 and to investigate disease trends following PCV13 introduction. Methodology: A retrospective cohort analysis of hospitalised patients with pneumococcal infection confirmed by blood culture and/or urinary antigen between January 2006 and December 2017. Clinical records, blood results, microbiological and radiological investigations were examined to identify patient characteristics associated with adverse outcomes including complications, ITU admissions and mortality. Mann-Whitney U and Chi-square were applied as appropriate. Results: 2114 admissions with pneumococcal disease were identified; (50% male, median age 66yr (IQR 51–79), 42% current smokers, 32% ex-smokers, 43% with chronic respiratory and 49% with cardiovascular disease). 92% (n=1948) admissions were pneumonia, 4% (n=82) meningitis, 1% (n=14) ENT-disease, 1% septic arthritis and 2% (n=41) other infections. Median length of stay was 7 days (IQR 5–10); all-cause inpatient mortality 16% (n=331); 1-year mortality 25% (n=521). 976 cases had causative serotype identified. Progressive serotype shift to non-PCV13 serotypes occurred (44% isolates pre-PCV13 versus 79% post-PCV13) (figure 1). Non-PCV13 serotype pneumonia increased from 47% pre-PCV13 to 98% post-PCV13 and meningitis from 65% to 100%. Total yearly patient admissions increased throughout the study ( P <0.05). Patient age, gender or smoking status was unchanged ( P -values>0.05). Median admission CURB65-score decreased throughout the study: 2 (IQR1–4) pre-PCV13 versus 2 (IQR1–4) post-PCV13 ( P <0.01). The proportion of patients with complications also decreased from 60% pre-PCV13 to 46% post-PCV13 ( P <0.01). ITU admissions increasing throughout the study ( P <0.01), but all-cause inpatient mortality decreased from 25% pre-PCV13 to 12% post-PCV13. However all-cause 1-year mortality remained 26% ( P >0.05). Conclusions: Serotype shift leading to increased disease from non-PCV13 serotypes occurred but disease severity may be decreasing. This may be due to serotype shift away from more invasive pneumococcal serotypes. Further investigation of the clinical impact of conjugate pneumococcal vaccination should be undertaken.